Seroprevalence of Antibodies Against Varicella-Zoster Virus Among Prevalent Hemodialysis Patients (Iranian Journal of Kidney Diseases, 2013)
Introduction. Varicella-zoster virus (VZV) can cause life-threatening disease in immunosuppressed patients, including kidney allograft recipients. This study was designed to evaluate the immune status of the cohort of hemodialysis patients, who could potentially be candidates for kidney transplantation, against VZV, and to determine the correlation between the self-reported history of chickenpox infection and the VZV antibody status in this population. Materials and Methods. Serologic testing for VZV was performed for 187 patients at different age groups receiving hemodialysis treatment at Hasheminejad Hospital, Tehran. The enzyme immunoassay method was used for determining immunoglobulin G antibodies against VZV. Results. A total of 187 patients, aged 18 to 88 years (mean, 57.5 ± 16.2 years), were examined. Ninety-five patients (50.8%) were men. Overall, 183 patients (97.9%) were found to be seropositive for VZV. No significant correlation was observed between patients' history of chickenpox disease and seropositivity of VZV. The sensitivity, specificity, and positive and negative predictive values of patients' self-reported history was 39.3%, 50%, 97.2%, and 1.7%, respectively. Conclusions. Serologic screening for VZV in patients who are candidates for transplantation is essential to determine their immune status prior to transplant surgery. We suggest that this population be considered as the target group for future immunization programs in Iran.